Distributed-order calculus: An operator-theoretic interpretation - Kochubei, A.N. (Український математичний журнал, 2008)
Within the Bochner – Phillips functional calculus and the Hirsch functional calculus, we describe the operators of distributed order differentiation and integration as functions of the classical differentiation and integration operators, respectively. У межах функціональних числень Boxнepa - Філліпса та Хірша наведено опис операторів диференціювання та інтегрування розподіленого порядку як функцій від класичних операторів диференціювання та інтегрування.